Differences of Pain among Children During Infusion in Buleleng Regency - Putu Wahyu Sri Juniantari Sandy; Aditha Angga Pratama (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Pain in children with treatment or management in the hospital is very common. Especially when seen when rehydrating children with infusions, almost all children are anxious, scared and crying. The purpose of this study was to see the difference in pain during infusion between those who were given the distraction of watching cartoons and those who were given conventional methods. Quantitative research method with quasi-experimental design. The sample used in the treatment and control groups was 34 respondents. The instrument uses a FLACC (Face, Legs, Activity, Cry and Consolability) pain scale sheet. Analysis using the Independent T-Test. The result is that there is a significant difference in pain from the treatment group to the control with a p value <0.005.